Assessing the Preoperative Neutrophil-Lymphocyte Count Ratio's Predictive Ability for Postoperative Sepsis in Percutaneous Nephrolithotomy Patients - Shariq Bin Yousuf, Bazgha Hassan, Shuah Ullah, Laraib Gul, Bilal Masood Khan, Asad Shahzad Hassan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The present study aimed to evaluate whether neutrophil lymphocyte count ratio (NLCR) can be used to detect post- PCNL sepsis.The objective of this study was to assess the potential of neutrophil-lymphocyte count ratio (NLCR) in detecting post-percutaneous nephrolithotomy (PCNL) sepsis. Methodology: The Department of Urology, Sindh Institute of Urology and Transplantation, Karachi, conducted a cross-sectional study between 05-Oct-2019 to 04-April-2020. Patients of renal stone planned for PCNL, All adult patients of age 18-65 years, irrespective of gender, those with the preoperative total leukocyte count of between 4 and 12 x109 cells/L, and those patients with ASA class 1 were made to take part in the study. After involving the patients in the study, CT KUB was used to calculate stone size. Complete blood Count was done one week before PCNL and NLCR was calculated for all patients. After PCNL, patients were followed for 1 week. All the gathered information including demographic details (age, gender), preoperative findings (NLCR, Stone size, staghorn), intraoperative findings (operating time, tracts, blood transfusion) and postoperative findings (temperature, heart rate, respiratory rate, total leukocyte count, blood and urine cultures) was noted on a pre-designed Proforma. Results: In this study, a total of 256 patients with a mean age of 41.17±10.18 years and a mean stone size of 29.1±6.3 mm were evaluated. The patients' mean operative time was 62.28±8.85 minutes. The area under the curve (AUC) was 0.824 in the ROC analysis, with the ideal cut-off value of NLCR being 2.5. The sensitivity and specificity of NLCR in predicting sepsis after PCNL were 50.0% and 98.0%, respectively, while the positive predictive value (PPV) was 80% and the negative predictive value (NPV) was 95.02%. The diagnostic accuracy was found to be 94.1%. Conclusion: The risk of sepsis following percutaneous nephrolithotomy (PCNL) can be predicted with success using a cut-off value of ≥2.5 for neutrophil-lymphocyte count ratio (NLCR). Moreover, it is a simple, cost-effective, and noninvasive test and readily available in hospital laboratories. Keywords: neutrophil lymphocyte count ratio, sepsis, percutaneous nephrolithotomy